Population dynamics of small mammals in the Jura massif, Franche-Comté, France (1979-2000) ... - Delattre, Pierre; Giraudoux, Patrick; Quéré, Jean-Pierre; Damange, Jean-Pierre (Zenodo, 2022)
Small mammal populations were monitored seasonally from August 1979 to July 2000 according to a stratified sampling plan and using standard trapping, mostly in the area of Septfontaines – Le Souillot, Doubs, France (6.18°E, 46.97°N). The dataset includes 2120 trap lines (90% n = 1912 in the Septfontaines – Le Souillot (LS) area), and 22848 captures (92% n = 20937 in the LS area). Methods Small mammals were captured using INRA trap lines. INRA live traps (15 × 5 × 5 cm) are suitable for species of body mass less than 50 g. In a standard way generally applied here,each trap line consisted of 34 live traps spaced 3 meters apart. Trap lines were set up for three nights and checked every morning. Animals were euthanized by cervical dislocation, weighed and dissected for sex, reproductive status and age determination. Liver was examined macroscopically for parasites. Relative age was estimated based on the dry weight of crystalline eye lenses. Caveats: in a very little number of cases (beginning of the study and ... : Pierre Delattre initialized and designed the study in the late 1970s, found financial support, and supervised the works; Patrick Giraudoux reorganized the sampling in 1987, computerized the data and maintained the database. Jean-Pierre Damange and Jean-Pierre Quéré provided technical assistance in the field and in the lab (trapping, dissections, crystalline lens weighing, etc.). All authors participated to field works, occasionally helped by a number of colleagues and students. ...